Small Cell Carcinoma of the Larynx Treated by Concurrent Chemoradiotherapy: A Case Report - Susumu Nakahara; Norihiko Takemoto; Hidenori Inohara (Case Reports in Otolaryngology)
Small cell carcinoma (SmCC) generally occurs in the lung and extrapulmonary SmCC is a relatively rare entity. Here, we present a case of a 42-year-old male with SmCC of the larynx diagnosed as cT3N0M0. Concurrent chemoradiotherapy using cisplatin (CDDP) and etoposide (VP-16) was given, which achieved complete response (CR). Lung metastasis became evident in 16 months whereas the locoregional control remained good. In spite of intensive chemotherapy using CDDP and irinotecan (CPT-11), the patient died of disease in 34 months after the first interview. Since the prognosis of laryngeal SmCC is extremely poor, organ preservation therapy should be considered instead of radical laryngectomy.